Implementation Strategy Fidelity and Organizational Outcomes in a Randomized Trial: Implications for Reentry from Corrections to Community Treatment. (23rd February 2023) - Stein, L. A. R.; Bassett, Shayna S.; Welsh, Wayne N.; Clair-Michaud, Mary; Abdel-Salam, Sami; Monico, Laura; Gallagher, Colleen; Murgo, Cecilia; Yang, Yang; Friedmann, Peter D.; Clarke, Jennifer G.; ,
Abstract: Background: This study examined fidelity of implementation strategies used in an organizational process improvement intervention (OPII) designed to improve evidence-based practices related to assessments for drug-involved clients exiting incarceration. Leadership was studied as a moderating factor between fidelity and outcomes. Methods: A mixed-method cluster randomized design was used to randomize 21 sites to early- or delayed-start within 9 research centers. Parent study protocol was reviewed to develop fidelity constructs (i.e., responsiveness, dose, quality, adherence). Outcomes were site-level success in achieving goals and objectives completed during the OPII (e.g., percent goals achieved). Correlations, analyses of covariance, regressions and moderation analyses were performed. Qualitative interviews assessed facilitators/barriers to implementation. Results: Fidelity constructs related to outcomes. No differences were found in fidelity by early or delayed condition. At low levels of leadership, high staff responsiveness (i.e., engagement in the OPII) related to poorer outcome. Conclusions: It is important to consider contextual factors (e.g., leadership) that may influence implementation strategy fidelity when deploying evidence-based practices. Findings are relevant to researchers, clinicians, administrators and policy makers, and suggest that goal completion during implementation of evidence-based practices requires monitoring of leadership competence, fidelity to implementation strategies (i.e., staff responsiveness to strategies) and attendance to goal importance.